Matematika dan Budaya Sasak: Kajian Etnomatematika di Lombok Timur - Kusaeri, Al; Pardi, Muhamad Habib Husnial (Universitas Hamzanwadi, 2019)
This research aims to identify the mathematical objects contained in the cultural products of the Kembang Kerang’s sosieties in East Lombok and its implementation in islamic educational institution. The research data was obtained by conducting cultural site studies as well as observations and interviews with informants who at the same time, became cultural actors and mathematics teachers at the research location. Results of the study show that cultural products were found in namely ragong gula gending, parane, kereng sesek, and caraken that contained the objects of mathematics in the form of flat building and building space consisting of links, cubes, tubes, squares, symmetrical flat shapes, and burial. Learning mathematics by utilizing Sasak cultural products carried out in islamic education institutions in MI NW Kembang Kerang shown good results on the implementation of learning, achieving ideal time of learning activities of students and teachers, positive responses from students after following the learning process, and changes in learning outcomes from before and after learning is done.